LOGICAL CONSISTENCY AND TOBACCO ECONOMIC DEVELOPMENT IN GRESIK REGENCY - Ciplis Gemah Qori'ah; Yulia Indrawati; Gigih Pratomo (UNEJ e-Proceeding, 2012)
Tobacco has a different potential in economic development efforts in an area. This justification is based on the tobacco plant is one that has economic value added [4]. Therefore we need a logical strategy in creating a positive impact on regional economic development. This study aims to formulate a strategy in economic development efforts of tobacco in Gresik Regency. This study uses primary and secondary data. The analyticalmethod used is descriptive analysis and Analytic Hierarchy Process (AHP). The results suggest that institutional and regulatory factors is a key strategy in the economic development of tobacco in Gresik Regency. The contribution of tobacco to the economy will provide a logical consistency in the development and cultivation of tobacco in the future.